Fabrication of porous carbons and mesoporous silica materials for energy storage and environmental applications - Sangchoom, Wantana (2016)
In the context of limited availability of fossil fuel and the impact of fossil-based energy utilization to the environment, novel porous materials have been extensively investigated for applications in environmentally friendly energy generation and storage. This thesis describes work wherein porous carbons and mesoporous silica materials have been systematically studied to include new synthesis strategies, material characterization. Two main themes of this thesis are, firstly, to investigate how porosity affects the utilization of activated carbons in energy storage and gas adsorption, and secondly, explore the stabilization of mesoporous silica materials. Chapter 1 discusses structures and classifications of pores. Porous carbons and mesoporous silica materials are introduced including the fundamental properties, preparation and important applications of the materials. Chapter 2 gives the basics of techniques used for characterization of the porous materials fabricated in this work. Gas sorption techniques applied for hydrogen storage and carbon dioxide uptake are introduced. The chapter also presents the electrochemistry and electrochemical methods used in this work. Chapter 3 briefly describes the preparation of highly porous carbons from lignin via hydrothermal carbonisation followed by chemical activation using KOH as activating agent. The work evidences the influence of activation temperature and KOH/carbon weight ratio on the structure of activated carbon and the performance of the gas storage capacity. Activation at KOH/carbon ratio of 2 generates highly microporous carbons which exhibit excellent CO2 uptake capacity; up to 4.6 mmol/g at 1 bar and 25 oC. Activation at KOH/carbon ratio of 4 can, on the other hand, generate lignin-derived carbons with ultrahigh porosity. These higher surface area lignin-derived carbons exhibit attractive hydrogen uptake capacity of up to 6.2 wt% at -196 oC and 20 bar. Chapter 4 is devoted to the use of lignin-derived activated carbons (LAC) as electrode materials for supercapacitors in aqueous and ionic liquid electrolytes. The study shows several factors affecting the electrochemical performance of carbon electrodes. It is demonstrated that a high surface area carbon (designated as LAC4800) electrode in 2 M H2SO4 exhibits a high capacitance value of 223 F/g or surface capacitance of 11.49 µF/cm2 and good cycling stability over 1000 cycles. The LAC electrodes also showed attractive capacitive performance with 175 F/g (6.92 µF/cm2) and the energy density can be enhanced in ionic electrolytes to reach 97.2 Wh/kg and power density of 2.0 kW/kg at 0.5 A/g for sample LAC4800 in BMImBF4 electrolyte. Chapter 5, regarding non-carbon materials, new forms of MCM-41 type silica mesostructures have been prepared by increasing the applied crystallization temperature to between 150 and 190 oC. The high temperature crystallisation resulted in enlargement of pore size and generated thicker pore walls. The sample prepared at 190 oC shows exceptional hydrothermal and thermal stability, even retaining long-range mesostructural ordering after refluxing in boiling water for 24 h or heating at 1000 oC for 4 h, which is unprecedented for pure silica MCM-41 materials. Finally, the conclusions for the thesis including the suggestion for future work are proposed in Chapter 6.